The Role of the Class II Sea and Coastal Guard Base Institution in Bitung City - Rhivan Fajrin Gobel; Evi Elvira Masengi; Goinpeace Tumbel (Technium Social Sciences Journal, 2025)
The purpose of the research is to find out, analyze and describe how the performance and role of the Class II Bitung Sea and Coast Guard Base (PLP) in maintaining providing rescue and providing shipping safety in sea and coastal waters. The research approach used in this research is a qualitative approach. The results showed that the facilities and infrastructure available at this time are still an obstacle in supporting the task optimally, coordination carried out by the Sea and Coast Guard Unit (KPLP) with other agencies is usually carried out in the form of conducting patrols at sea and conducting some preparedness training to carry out search and rescue operations in the event of a sea transportation accident. There is still a lack of public understanding of the importance of shipping rules and safety at sea. For example, some local fishermen do not equip their boats with standard safety equipment such as life jackets or navigation tools. Based on the research results that have been presented above, it can be concluded that the performance and role of the Bitung Class II PLP Base in maintaining providing rescue and providing shipping safety in sea and coastal waters can be said to be not optimal due to the available funds are not always sufficient to meet the needs of ship maintenance, purchase of new equipment, or operational costs of routine patrols, joint patrols at sea involving various parties to increase supervision coverage and efficiency in enforcing shipping rules and preparedness training to prepare for search and rescue operations in the event of a marine transportation accident and low awareness and knowledge of fishermen about the importance of the availability of safety equipment such as life jackets. Another factor is the economic factor where economic limitations make fishermen reluctant to spend additional costs to buy safety equipment.